Annotated catalogue of the Iranian broad-headed bugs (Hemiptera: Heteroptera: Alydidae) - Ghahari, Hassan (2010)
The fauna of Iranian broad-headed bugs (Coreoidea: Alydidae) is studied in this paper. A total of twenty-one species of eleven genera (Alydus Fabricius, 1803, Camptopus Amyot & Serville, 1843, Euthetus Dallas, 1852, Heegeria Reuter, 1881, Megalotomus Fieber, 1860, Mirperus Stål, 1860, Nariscus Stål, 1865, Nemausus Stål, 1866, Riptortus Stål, 1859, Tenosius Stål, 1860, Leptocorisa Latreille, 1829) belonging to two subfamilies (Alydinae, Leptocorisinae) are listed for Iranian fauna. Out of them, three species, Megalotomus junceus (Scopoli, 1763), M. ornaticeps (Stål, 1858) and Leptocorisa oratoria (Fabricius, 1794), are new records for Iran.